Employment-related mobility and migration, and vocational education and training - (:unkn) unknown (Publications Office of the European Union, 2011)
In the European labour market, worker mobility can help address regional imbalances. This report focuses on the difficulties migrant workers face in making their way in the destination country labour market. It reviews ReferNet research reports from several European countries on the problems migrant workers face, and examines whether these workers could benefit from vocational training. The answer is a tentative 'yes'. Difficulties in the labour market can often be due to a lack of social capital, i.e. the network of contacts that help individuals to move proficiently within a social environment. Training institutions which involve social partners and local communities can effectively fill this gap for migrant workers. (BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 2.1 Globalisierung; G 1.3.3.3 Mobilität; I 2.2 Europa; Arbeitsmarkt; Mobilität; Wanderung; Berufsbildung; Europa